On-site sequencing of SARS-COV-2 genomes identify two variant of concern clusters in Pahang, Malaysia - Zainulabid, Ummu Afeera; Wan Ramli, Wan Nurliyana; Haroon, Raihanah; Aslam, Ayesha; Hussain, Mushtaq; Ahmad, Hajar Fauzan (Faculty of Industrial Sciences and Technology at Universiti Malaysia Pahang, 2023)
Timely variant identification is required in respond to effective public health measures. It has been demonstrated that comprehending genetic epidemiology can be aided by a combination of public health expertise and through viral genomic sequencing using Oxford Nanopore Technologies (ONT). The purpose of this study is to determine the utility of using Oxford Nanopore Sequencing to elucidate the genetic epidemiology in two significant clusters in Pahang, Malaysia. The combined oropharyngeal and nasopharyngeal swabs of clinical specimens from two significant clusters in Pahang, Malaysia, were retrieved for long-read sequencing. Results: We identify Beta and Delta variants as 2 variants of concern from our analysis. We found that the B.1.351 (ß) and B.1.617 (D) variants were responsible for the Taman Tanah Putih Baru and Pasar Kemunting clusters, respectively. In conclusion, ONT long-read sequencing tools offer a practical solution with a number of advantages. ONT devices are compact, affordable, and need little technical hands-on or laboratory equipment to prepare samples. They can also be used to quickly and adaptably execute sequencing analyses and to understand genomic epidemiology.